Anonymous
Anonymous asked in Science & MathematicsMathematics · 7 years ago

|A|∙|B|=|AB| Matrix Component Proof?

Hello all,

I am preparing for an exam tomorrow and we have been asked to prove that the determinant of square matrix 'A' multiplied by the determinant of square matrix 'B' is equal to the determinant of the product of matrix 'A' and matrix 'B'. The proof must be in terms of components (i.e. in terms of a_ij and b_ij).

Any help would be greatly appreciated!!

Grateful Student

3 Answers

Relevance
  • Eugene
    Lv 7
    7 years ago
    Favorite Answer

    Andrew, are you assuming A and B are general n x n matrices, or are you proving this for a special case? Just in case, I'll work with n x n matrices. Let A = (a_ij) and B = (b_ij). Then AB = (c_ij), where c_ij = ∑(k = 1, n) a_ik b_kj. Hence

    |AB| = ∑(p ∈ Sn) sign(p) c_1p(1) ••• c_np(n)

    = ∑(p ∈ Sn) sign(p) (∑(k(1) = 1, n) a_1k(1) b_k(1)p(1)) ••• (∑(k(n) = 1, n) a_nk(n) b_k(n)p(n))

    = ∑(k(1) = 1,n) ••• ∑(k(n) = 1, n) (a_1k(1)••• a_nk(n)) ∑(p ∈ S(n) sign(p) (b_k(1)p(1) ••• b_k(n)p(n)).

    = ∑(k(1),..., k(n) = 1, n) (a_1k(1) ••• a_nk(n)) |b_k(i)j| (*)

    Now if there exist l and m such that k(l) = k(m), then the matrix (b_k(i)j) has two equal rows and |(b_k(i)j)|= 0. So the sum in (*) is equal to the sum over all n-tuples (k(1),...,k(n)) where each of k(1),...,k(n) are distinct. Given such an n-tuple, there exists a permutation q ∈ Sn such that q(i) = k(i) for all 1 ≤ i ≤ n. Conversely, given a permutation q ∈ Sn, the elements q(1),...,q(n) are distinct. Hence the sum in (*) is equal to

    ∑(q ∈ Sn) (a_1q(1) ••• a_nq(n)) |(b_q(i)j)|

    = ∑(q ∈ Sn) (a_1q(1) ••• a_nq(n)) • sign(q) |(b_ij)|

    = ∑(q ∈ Sn) sign(q) a_1q(1) ••• a_nq(n) • |B|

    = |A| |B|.

  • Jeff
    Lv 7
    7 years ago

    Hint: Resort to the definition of determinant

  • 7 years ago

    A=___and B=

    (a c)______(e g)

    (b d)______(f h)

    so

    AB=

    (ae+cf ag+ch)

    (be+df bg+dh)

    then

    det(AB)= (ae+cf)(bg+dh) - (be+df)(ag+ch)

    = (abeg + adeh + bcfg + cdfh)

    _______ - abeg - bceh - adfg - cdfh

    = abeg - abeg + cdfh - cdfh +

    ________+ (ad - bc)eh - (ad-bc)fg

    so

    det(AB) = (ad-bc)(eh-fg)

    finally

    det(AB) = det(A) . det(B)

    et voilà !!

    hope it' ll help !!

    if you ' ve found this answer useful, please choose it as best answer.

Still have questions? Get your answers by asking now.